The Relationship of Proto Austronesian (PAN) and Minangkabau Languages (Comparative Historical Linguistic Studies) - Akmal Akmal; Suparmadi Suparmadi; Zulkarnain Sirait (Aksara: Jurnal Ilmu Pendidikan Nonformal, 2023)
This study was languages focused on comparative historical linguistics. The comparisons between two or more languages can be said to be age-appropriate with the emergence of linguistics itself. Understanding of a language is very interesting to know the extent to which there are similarities or similarities between aspects of the language that discussed the relationship of Proto Austronesian and Minangkabau. This study used the descriptive quantitative research design. These data were taken from the corpus (internet document) and also went to the field by interviewing the native speakers of the Minangkabau language. The researchers have found 97 related vocabularies that consist of 36 identical pairs, 27 pairs that had phonemic correspondences, 25 phonetic similarities, and 9 different phonemes. After calculating the percentage of kinship, the result of kinship is 49%. That means the kinship between the Proto-Austronesian language and the Minangkabau language is very close. From the findings of the related vocabularies, it could be explained that the Proto-Austronesian and Minangkabau languages are very close because they have had more than 20 % (twenty percent).